Vajdaság gazdasági életének alakulása az 1980-as években - Bakó Tamás (2019)
Economic development policy of the Autonomous Province of Vojvodina was determined by the industrialization process that took place between 1947 and 1980 when fast industrialization at “any price” was typical. Within the province of Vojvodina, the share of agriculture fell from 43.4% in 1952 to 26.5% in 1984, while the share of industry in this period rose from 21.8% to 38.6%. The product market supply was “western” in the eyes of Eastern Central Europe, and the competitiveness and productivity of the industry and food industry in the 70s and 80s was a major export success. Deficiencies appeared on the supply market, but business and technology innovations somewhat compensated for the limited supply of goods (there are few products in the stores offering goods, but its quality is Western-European). As small farms were unable to compete with large-scale production, and in addition, the “trademark” of organic and small producers did not exist at this time, the forced industrialization has caused serious difficulties for the population of villages and rural areas in many respects. The former industrial centers in Vojvodina either ceased to exist or lost their function, “restructured”, the population living there remained unemployed, but the “absorbing effect” of the food industry provided a kind of social balance, a secure job. In Vojvodina, as a result of the process beyond its age, production and service have reached almost the same level in the 1980s. Between 1952 and 1990, Yugoslavia had the fastest GDP growth in Vojvodina (6.2-fold increase).